(untitled) (Journal of the College of Basic Education, 2024)
acquiring grammatical in other branches of the Arabic concepts among fourth-grade literary students."In order to verify the aim of the research, the researcher put the following zero hypothesis:"There is no statistically significant difference between the mean scores of students in the experimental group who study grammatical concepts using the (Koscroft) model and the average scores of students in the control group who study grammatical concepts in the traditional way" in the post-test.The researcher followed the experimental approach and adopted an experimental design with partial control, which is the design of the experimental group and the control group with random selection.The researcher randomly chose her research sample consisting of (63) preparatory students (Al-Khansa for girls) affiliated to the General Directorate of Education, Al-Rusafa 1 in Baghdad Governorate, with (32) students in the experimental group and (31) students in the control group.The researcher rewarded the female students of the two research groups in the following variables: (the chronological age calculated in months, the academic achievement of fathers and mothers, and grades of the Arabic language for the previous academic year in the third average. Then the researcher tried to control a number of extraneous variables that the previous literature indicated may affect this type of experimental design.The researcher studied by herself the students of the two groups, the experimental one according to the (Koscroft) model, and the control group using the traditional method, during the experiment period, which lasted one semester, which is the first semester of the academic year 2022-2023 AD.The researcher prepared a final test as a tool for her research, consisting of (30) items of the multiple choice type, which she applied to the experimental and control research groups at the end of the experiment, and the researcher used the appropriate statistical methods for her research procedures, which are Man, Whitney and the Samir Nof test for two independent samples, and after processing the data statistically, it was The result is that there is a statistically significant difference at the level (0.05) between the mean scores of the students of the two research groups in acquiring grammatical concepts, in favor of the experimental group.